SCREENING OF 110 CIRRHOTIC PATIENTS FOR HEPATITIS B AND C AT SAIDU TEACHING HOSPITAL SAIDU SHARIF SWAT - Khan, Purdil; Ahmad, Aziz; Muhammad, Noor; Khan, Taj Muhammad; Ahmad, Bilal (Journal of Ayub Medical College Abbottabad, 2009)
Background: Cirrhosis liver is amongst the commonest clinical conditions in Pakistan. Besides other causes, it is mostly related to previous viral infection, in this part of the world. The main objective of this study was to find the frequency of HBsAg and anti HCV in cirrhotic patients of Swat district. Methods: This Prospective Study was conducted in the Medical unit of Saidu Teaching Hospital, Saidu Sharif from January 2006 to December 2006. One hundred and ten Cirrhotic Patients, 62 Male and 48 Female aged from 14 to 75 years were included in this study. Sera were tested by 3rd generation Elisa method. Results: Fifty-nine out of 110 (53.6%) patients were positive for anti HCV antibodies. Twenty-four (21.81%) Patients were positive for HBsAg. Eleven (10%) patients were positive for both HBsAg and anti HCV anti bodies. Sixteen (14.54%) were negative for both sero maker of hepatitis B and C. Conclusion: It is evident from this study that Hepatitis C, is a leading cause of cirrhosis in District Swat followed by HBV. Both the viruses account for at least three fourths of the total Cirrhotic. Keywords: Cirrhosis liver, HBsAg, Anti HCV